The Types of Slang Words Used in the Chat Feature of Mobile Legends Game - Lasma; Meristika Moetia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Slang has become an essential feature of communication in online gaming, allowing players to exchange information quickly and efficiently during gameplay. However, studies examining the linguistic characteristics of slang in Mobile Legends chat remain limited. Therefore, this study aims to identify, classify, and analyze the frequency of slang words used by players in the chat feature of Mobile Legends. This research employed a descriptive qualitative method. The data were collected from chat interactions in nine Mobile Legends matches conducted between April 13 and May 21, 2026, using observation and documentation techniques through screenshots of in-game conversations. The data were analyzed by classifying the slang words into four categories based on the theoretical framework utilized in this study: acronyms, abbreviations, clippings, and game-specific slang. The findings identified a total of 77 slang words, consisting of 35 acronyms, 27 game-specific slang terms, 10 clippings, and 5 abbreviations. Acronyms were the most frequently used type because they enabled players to communicate rapidly in a fast-paced gaming environment, while game-specific slang reflected players’ shared understanding of game mechanics and strategies. The findings indicate that slang functions not only as an efficient communication tool but also as a linguistic marker of identity within the Mobile Legends gaming community. This study contributes to sociolinguistic research by providing empirical evidence of the use and variation of slang in online gaming communication.